Fatores clínicos e epidemiológicos associados aos transtornos de controle de impulsos e condições relacionadas na doença de Parkinson - Antonio Pedro Vargas (2018)
Introduction: Pharmacological treatment of Parkinson's disease (PD) is primarily symptomatic. Dopaminergic therapy may induce undesirable effects. In recent years, behavioral changes characterized by impulsivity (impulse control disorder - ICD), repetitive unintentional behaviors (punding) and compulsive use of dopaminergic medication in doses above the therapeutic need, with symptoms of intoxication and hypomanic state (Dopaminergic Dysregulation Syndrome - SDD), have been described. These conditions have clinical and pathophysiological similarities with substance abuse disorders and may be considered as behavioral addiction disorders related to the use of levodopa or dopaminergic agonists. Its pathophysiology is still not fully understood, but it seems to be related to abnormal dopaminergic stimulation in the ventral regions of the basal nuclei, mainly by the nigro-mesolimbic pathways. Objective: The aim of this study was to verify the prevalence in PD patients of ICD (and its most frequent types), SDD, and punding; the associated clinical and demographic factors, including severity, disability; relationships with other neuropsychiatric disorders, socioeconomic factors, and use of dopaminergic drugs. Methods: A case-control study was carried out in 207 PD patients consecutively admitted at the neurology outpatient clinic of SARAH Rehabilitation Hospitals in Belo Horizonte and Rio de Janeiro. A control group was composed of 230 family members or caregivers of patients undergoing treatment at the neurological rehabilitation program in the same hospitals. UPDRS was used to evaluate PD clinical aspects. The Hoehn & Yahr scale was used to assess the severity, and of Schwab and England scale of daily living activities, the disability. Information regarding the socioeconomic profile, drug use, comorbidities, and family history of the patients and the control group were obtained through an interview using a structured questionnaire developed by the authors. Cognitive evaluation was using Mini-Mental State examination, FAB, and SCOPA-cog. Presence of neuropsychiatric disorders, including mood disorder, obsessive-compulsive disorder, anxiety, psychosis, antisocial personality disorder, alcohol dependence/abuse, and psychoactive substances addiction were screened by MINI-PLUS. The Geriatric Depression Scale and Beck Depression Inventory were used to assess the presence of mood disorder. The diagnosis of SDD, ICD and punding was made based on clinical criteria, after application of the Minnesota Impulsive Disorders Interview for screening. Patients with and without compulsive-impulsive disorders were initially compared to each other, and later to the control group. A descriptive statistic was made to obtain the characteristics of the study population and the prevalence of the described variables. Fisher's exact test and the t-student test were used for univariate analysis of the association between variables. All independent variables with a significance level of 0.80 (p <0.20) were tested for logistic regression and the level of significance was considered at p <0.05. Results: ICD was identified in 16.9% of the patients (compulsive buying in 7.7%, binge eating in 6.7%, gambling disorder in 5.8%, hypersexuality in 4.3%, more than one ICD in 5.8%); Punding in 5.3%, and SDD in 3.4%. The frequency of ICD in the control group was 15.2%. (p = 0.631). Punding was more frequent in PD (p = 0.028). However, ICD was more frequent in patients with PD who took dopaminergic agonists than in patients who did not take them (p = 0.001) and in the control group (p = 0.014). ICD was more common in patients taking dopaminergic agonist, especially if they were taking high doses (the estimated risk of ICD increases about 23% to each pramipexole 0.25 mg tablet). Additional variables associated with ICD were: antecedent of gambling disorder (p <0.001), antisocial personality disorder (p = 0.019), SDD (p = 0.015), moderate disability (50% -70%) as measured by Schwab and England activities of daily living scale (p = 0.002); low semantic fluency (p = 0.002), and better performance in the backward digit span (p = 0.002). Family history of PD decreased the risk of ICD (p = 0.013). Punding was associated with unmarried state (p = 0.004), current or previous smoking (p = 0.009), increasing dyskinesias duration (p = 0.02), antisocial personality disorder (p = 0.006), and moderate disability (50% -70%) as measured by Schwab and England activities of daily living scale (p = 0.005). SDD was associated with dyskinesias (p = 0.020), and psychotic disorder (p = 0.022).